2022
DOI: 10.3390/jmse10040479
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Irradiance and Nutrient Enrichment Mitigate the Negative Effect of Ocean Warming on Growth and Biochemical Compositions of a Canopy-Forming Marine Macroalga

Abstract: Heatwaves under global warming have negative impacts on ecosystem primary producers. This warming effect may be synergized or antagonized by local environments such as light and nutrient availability. However, little is known about the interactive effects of warming, irradiance, and nutrients on physiology of marine macroalgae, which are dominant in coastal ecosystems. The present study examined the combined effects of warming (23 and 26 °C), irradiance (30 and 150 µmol photon m−2 s−1), and nutrients (enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Charan et al [ 27 ] reported that the negative effect on shoot growth in S. fusiforme caused by summer temperature increasing from 23 to 26 °C was synergized by the co-occurring increase in irradiance from 30 to 180 µmol photons m −2 s −1 , probably because excess light energy under warm temperature caused photoinhibition of this species [ 29 ]. Similarly, in the present study, the negative effect on shoot growth in S. nipponicum caused by temperature increasing from 20 to 30 °C was synergized by irradiance increasing from 30 to 130 µmol photons m −2 s −1 , although the mean growth rates were negative at 30 °C even at the lowest irradiance level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charan et al [ 27 ] reported that the negative effect on shoot growth in S. fusiforme caused by summer temperature increasing from 23 to 26 °C was synergized by the co-occurring increase in irradiance from 30 to 180 µmol photons m −2 s −1 , probably because excess light energy under warm temperature caused photoinhibition of this species [ 29 ]. Similarly, in the present study, the negative effect on shoot growth in S. nipponicum caused by temperature increasing from 20 to 30 °C was synergized by irradiance increasing from 30 to 130 µmol photons m −2 s −1 , although the mean growth rates were negative at 30 °C even at the lowest irradiance level.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study reported that S. fusiforme propagules exhibited positive growth rates at 30 °C in nutrient-enriched seawater but negative values at the same temperature in nutrient-poor natural seawater, while its holdfasts without shoots showed positive growth rates even at 32 °C in natural seawater [ 11 ]. Additionally, the negative effect of elevated summer temperatures on the growth rate of S. fusiforme shoots has been shown to be antagonized by decreased irradiance [ 27 ]. However, no study has comprehensively evaluated the effects of temperature, irradiance, and nutrient conditions on growth (including holdfast growth, shoot emergence from holdfasts, and shoot growth) during summer in either S.fusiforme or S. nipponicum .…”
Section: Introductionmentioning
confidence: 99%